1985
DOI: 10.1002/bms.1200120903
|View full text |Cite
|
Sign up to set email alerts
|

Laser microprobe mass analysis: A review of applications in the life sciences

Abstract: The characteristics and analytical utility of laser microprobe mass analysis (LAMMA) are described and evaluated, and a short history of this recent microanalytical technique is presented. A review of the areas of application of LAMMA and related laser microprobes is presented with special emphasis on applications in the life sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 137 publications
0
11
0
Order By: Relevance
“…The theoretical principles of in situ analytical techniques are beyond the scope of the present review; interested readers can find more information about: EDXMA in Chandler (1979); SIMS in Linton et al (1980); LAMMA in Denoyer et al (1982) and Verbeuken, Bruynseels & Van Grieken (1985). Briefly, all these techniques rely on bombardment of the specimen with a beam of either ions (SIMS and PIXE), electrons (EDXMA) or photons (LAMMA), causing either ejection of surface atoms/ ions, which are analysed by mass spectrometry (SIMS and LAMMA), or knocking out of certain shell electrons that give rise to element-specific primary X-rays (EDXMA and PIXE).…”
Section: In Situ Techniques For Measurement Of Aluminiummentioning
confidence: 99%
“…The theoretical principles of in situ analytical techniques are beyond the scope of the present review; interested readers can find more information about: EDXMA in Chandler (1979); SIMS in Linton et al (1980); LAMMA in Denoyer et al (1982) and Verbeuken, Bruynseels & Van Grieken (1985). Briefly, all these techniques rely on bombardment of the specimen with a beam of either ions (SIMS and PIXE), electrons (EDXMA) or photons (LAMMA), causing either ejection of surface atoms/ ions, which are analysed by mass spectrometry (SIMS and LAMMA), or knocking out of certain shell electrons that give rise to element-specific primary X-rays (EDXMA and PIXE).…”
Section: In Situ Techniques For Measurement Of Aluminiummentioning
confidence: 99%
“…This method is also at low cost, with respect to the other point-like methods as X-ray fluorescence spectroscopy, or neutron activation method. The method was used early in the metallurgy [3], inorganic material investigation [3,4], archeology and museum investigation [5,6,7], analysis of the paintings and sculptures [8,9], medicine and biology [10][11][12][13][14][15]. In the medical field it was studied the composition of the dental implants [10], of the super thin layers [10], of the bones in different regions [11], of hair [12], and so on.…”
Section: Laser Microspectral Analysis In Dentistrymentioning
confidence: 99%
“…There are several methods which may be classified as LDI MS approaches that have unique names, including laser microprobe mass analysis (LAMMA) [45] and laser microprobe mass spectrometry (LMMS) [46]. For many years, LDI MS has been successfully applied to profiling the biochemical composition of different tissues and cells [47][48][49][50][51] with several examples of LDI MSI being used to examine nervous system-related specimens [35,52]. In one of these, Todd et al [35] demonstrated that the antipsychotic drug, clozapine, which interacted specifically with the 5-HT 2 receptors after its injection into the tail vein of a rat, accumulated in the striatum and cerebral cortex but not in the corpus callosum.…”
Section: Desi Ms Ldi Ms La-icp Ms and Maldi Ms Imagingmentioning
confidence: 99%